Democracy Education for Children using a Cartoon Video and Mock Voting - Jun Makita (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2021)
In democracy education, determining how best to teach young children about democracy and how to measure the effectiveness of such learning is difficult, as